PELAKSANAAN SYARIAT ISLAM PADA QANUN NOMOR 11 TAHUN 2002 BIDANG AQIDAH, IBADAH, DAN SYIAR ISLAM - Mariadi (IAIN Langsa, 2018)
Wilayatul Hisbah in Aceh stand hand in hand with the implementation of the Islamic jurisprudence requiring the Agency supervisor. The existence of this institution has been legally valid through Qanun number 11 2002 Article 14 of Chapter VI and Qanun No. 12 of 2003 article 16 to 18. Then in the next series of Qanun mentioned authorities and provisions charged to the Wilayatul Hisbah as the catalyst for the success of the Islamic Sharia in Aceh. In law number 11 of 2006 about Aceh Government, strengthen the presence of Wilayatul Hisbah not only as an overseer of the Shari'ah of Islam but more than it did the enforcement of qanun-qanun field of Islamic Shari'ah. It can be seen in section 244 subsection (2) of ACT No. 11 of 2006 explicitly states that the function of the Wilayatul Hisbah is ideal as a special police enforcing Islamic Sharia qanun-qanun. As part of the supervisory enforcement actions i.e. conduct surveillance against laws and violation of execution of invitation in the field of Islamic jurisprudence. This is a qualitative Research method using a descriptive analytical methods that describe and analyze problems expressed that aims to describe in concrete Wilayatul Hisbah. About the role of the research Specification i.e. the legal research that uses this type of Normative legal research also assisted with legal research or Empirical Sociological legal research. Primary data, i.e. data obtained directly from informants as a source in the research field in the form of interviews, documents, while the secondary data source i.e., from books, legislation, journals etc., to look at the role of the Wilayatul Hisbah in enforcement qanun No. 11 of 2002 on the implementation of the Islamic Shari'a field of Aqidah, worship, and rituals of Islam in Langsa.